Kukaa Salama (Staying Safe): study protocol for a pre/post-trial of an interactive mHealth intervention for increasing COVID-19 prevention practices with urban refugee youth in Kampala, Uganda - Logie, Carmen H.; Okumu, Moses; Hakiza, Robert; Musoke, Daniel Kibuuka; Kyambadde, Peter; Mwima, Simon; Baral, Stefan (BMJ open, 2021)
With over 82.4 million forcibly displaced persons worldwide, there remains an urgent need to better describe culturally, contextually and age-tailored strategies for preventing COVID-19 in humanitarian contexts. Knowledge gaps are particularly pronounced for urban refugees who experience poverty, overcrowded living conditions and poor sanitation access that constrain the ability to practise COVID-19 mitigation strategies such as physical distancing and frequent hand washing. With over 1.4 million refugees, Uganda is sub-Saharan Africa’s largest refugee hosting nation. More than 90 000 of Uganda’s refugees live in Kampala, most in informal settlements, and 27% are aged 15–24 years old. There is an urgent need for tailored COVID-19 responses with urban refugee adolescents and youth. This study aims to evaluate the effectiveness of an 8-week interactive informational mobile health intervention on COVID-19 prevention practices among refugee and displaced youth aged 16–24 years in Kampala, Uganda. We will conduct a pre-test/post-test study nested within a larger cluster randomised trial. Approximately 385 youth participants will be enrolled and followed for 6 months. Data will be collected at three time points: before the intervention (time 1); immediately after the intervention (time 2) and at 16-week follow-up (time 3). The primary outcome (self-efficacy to practise COVID-19 prevention measures) and secondary outcomes (COVID-19 risk awareness, attitudes, norms and self-regulation practices; depression; sexual and reproductive health practices; food and water security; COVID-19 vaccine acceptability) will be evaluated using descriptive statistics and regression analyses.
Keywords: Staying Safe; COVID-19; mHealth intervention